Integrasi Teknologi dalam Pendidikan Islam:: Analisis Bibliometrik dan Pemetaan Konseptual (2015-2024) - Slamet Riyadi; Rozaanah; Naser Ali Abdulghani (Tasqif: Journal of Islamic Pedagogy, 2025)
Digital transformation in Islamic education faces dialectical challenges in maintaining the authenticity of spiritual values while integrating contemporary technological innovations. This study aims to map conceptual networks, analyze temporal trends, and identify research gaps in Islamic digital pedagogy through a comprehensive bibliometric analysis. It employs a mixed-methods approach combining a systematic literature review with bibliometric analysis using VOSviewer on 175 keywords from Scopus and Web of Science publications from 2015 to 2024. The Boolean search strategy combines Islamic education terminology with educational technology. The analysis identified three dominant clusters: Cultural-Philosophical Foundation, Tech-Driven Education, and Traditional Islamic Pedagogy. Critical findings reveal a significant disconnect between AI technological innovations (Cluster 5) and the Islamic pedagogical context (Cluster 9), with a distance coefficient of 0.23 (on a scale of 0-1, where 0 indicates a high level of connection and 1 indicates a lack of connection). The temporal evolution shows three distinct phases: Foundation Building (2015–2019), Pandemic Response (2020–2022), and AI Integration Era (2023–2024). Critical research gaps have been identified in the application of generative AI for Islamic content analysis (density 0.12 = very low), virtual reality for Islamic history education (density 0.08 = very low), and AI-assisted Arabic language learning (density 0.18 = low). Density values <0.30 indicate highly under-explored areas. Research fragmentation reveals fundamental epistemological tensions between the Islamic knowledge paradigm and secular technological frameworks. The development of an integrated theoretical framework prioritizing the principles of maqasid al-syariah in evaluating the integration of Islamic educational technology is necessary.